2018
DOI: 10.1159/000492919
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Time after Hemodialysis Is Inversely Associated with the Ultrafiltration Rate

Abstract: Introduction: The present study aimed to determine the variables that are associated with a longer dialysis recovery time (DRT) and to define the relationship that exists between DRT and the ultrafiltration rate (UFR) in prevalent chronic hemodialysis (CHD) patients. Methods: We studied 210 prevalent CHD of 5 hemodialysis units in Central Italy. Patients were invited to answer to the question: “How long does it take you to recover from a dialysis session?” Answers to this question were subsequently converted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
20
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 28 publications
9
20
4
1
Order By: Relevance
“…We also found that the PDF intensity and the Sum Score were negatively associated with the UFR. This is in accordance with a recent study that has shown that the recovery time after the dialytic session was inversely related with UFR, with the highest tertile of recovery time being associated with an UFR below the mean value (Bossola et al 2018c). The finding that the Sum Score is negatively associated with UFR is particularly interesting and, to the best of our knowledge, is the first time that is reported.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that the PDF intensity and the Sum Score were negatively associated with the UFR. This is in accordance with a recent study that has shown that the recovery time after the dialytic session was inversely related with UFR, with the highest tertile of recovery time being associated with an UFR below the mean value (Bossola et al 2018c). The finding that the Sum Score is negatively associated with UFR is particularly interesting and, to the best of our knowledge, is the first time that is reported.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, we found no difference in the prescription of dialysate potassium and dialysis-associated symptoms [8]. Symptoms associated with low blood pressure were then next most commonly reported, and several previous studies have reported a strong association between ultrafiltration rates and post-dialysis fatigue [15,34,35]. However, these studies were typically reporting much high ultrafiltration rates of > 9 mL/kg.h compared to our patients, and we found no association with changes in systolic blood pressure or pre-dialysis NT-proBNP.…”
Section: Discussionsupporting
confidence: 70%
“…Compared to previous studies, our patients reported relatively fewer symptoms [15,16,35]. This may have been due to the use of convective clearance with haemodiafiltration rather than conventional haemodialysis [13], or the colder dialysates [9], or lower ultrafiltration rates used in our study cohort [15,[33][34][35].…”
Section: Discussionmentioning
confidence: 64%
“…Systolic blood pressure fell to 90 mmHg in 12 patients (< 2%) and less than 100 mmHg in 42 patients (7%). In both cases lower nadir blood pressure was more common in female patients (X 2 10, p = 0.002; X 2 9.7, p = 0.02, respectively), and although individual symptom scores did not differ, total symptom scores were greater for those with a nadir systolic blood pressure of than 90 mmHg or lower (42.5 (21.5-61.5) vs 23 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), p = 0.03) and with a nadir of 100 mmHg or less (22 (12-36) vs 13 (5-21) , p = 0.003). Time to recover reported was also longer for those patients with a nadir systolic blood pressure of than 90 mmHg or 100 mmHg compared with those with higher systolic blood pressures (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…*p < 0.05, vs those with an increase in SBP of > 10 mmHg with a nadir systolic blood pressure of 90 mmHg or lower was relatively small, we reviewed the symptom scores from those patients with asymptomatic hypotension [18,19]. These patients had a greater percentage weight loss, which would be in keeping with reports of higher ultrafiltration rates leading to more post-dialysis fatigue [26]. However, the ultrafiltration rates used in our patient cohort were much lower than those previously reported, and as such in our study, there was no statistically significant association [27].…”
Section: Discussionmentioning
confidence: 89%